Descrição e classificação das construções conversas do Português do Brasil - Calcia, Nathalia Perussi (Universidade Federal de São Carlos, 2016)
This dissertation proposes an analysis about the relation between pairs of constructions, both with support-verb and predicative name, such as João deu uma ajuda ao Pedro/Pedro recebeu uma ajuda do João. This relation is called Conversion (G.GROSS, 1989), a transformational property that inverts the arguments of the subject position and the phrase complement, without changing their semantic roles, restructures a sentence inverting sense from active to passive. Thus, by inverting the standard support-verb (dar, fazer ou ter – to give, to do or to have) for a converse support-verb (receber, levar or ter – to receive, to lead or to have), the conversion produces equivalent syntactic-semantically sentences. The analysis of this type of construction is done systematically, based on Transformational Grammar (HARRIS, 1964) and theoretical-methodological model of Lexicon-Grammar (M.GROSS 1975, 1981), adopting formal criteria of linguistic description. The proposed classification is based on the set of support-verbs that each predicative noun selects such in the standard position, as in converse position. This criterion proved to be the most appropriate at this moment, because the predicative nouns constitute a very heterogeneous group, by the syntactic-semantic point of view. The sentences that exemplify constructions converses are validated introspectively and through of a corpus, where it can identify its structure with better precision. In addition, their structural, distributional and transformational properties are formalized in a table of Lexicon-Grammar, that is, is a binary matrix in which each row corresponds to a lexical entry (the predicative noun) and each column corresponds to a formal property of the construction. Therefore, this study aims to contribute to the linguistic description of Brazilian Portuguese, taking into account that this type of construction was studied only for the French (G.GROSS, 1989), European Portuguese (BAPTISTA, 1997) and more recently to the Romanian (CIOCANEA, 2011). The constructions description with support-verb and predicative noun, may collaborate in texts analysis, identifying information and the structure‘s form, then, consequently, enriching the description of the language. Besides, the results‘ representation in binary matrixes provides a formal description enough to be used in auto applications in Natural Language Processing (NLP).
Keywords: Conversão; Construção conversa; Verbosuporte; Nome predicativo; Léxico-gramática; Conversion; Construction converse; Support verb; Predicative noun; Lexicon- Grammar; LINGUISTICA, LETRAS E ARTES::LINGUISTICA